2021
DOI: 10.1186/s42155-021-00212-y
|View full text |Cite
|
Sign up to set email alerts
|

Shape memory polymer ovarian vein embolisation in a patient with nickel allergy

Abstract: Background Ovarian vein embolization in pelvic varicocele is usually obtained using nitinol coils. These devices can not be used in patients with proven nickel allergy. Case presentation Shape memory polymer is a new embolic material available to interventionalists. A patient presented with pelvic congestion syndrome requiring embolisation of the left ovarian vein. The target vessel consisted of two twisted branches, each 5–6 mm in diameter. The pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The expanded form has a high surface area and supports thrombus formation throughout its structure. The use of embolic devices based on shape memory polymer in the peripheral vasculature and aorta has been reported 13–15. The shape memory polymer is bioabsorbable,16 although the timeline for absorption is unknown in human clinical cases.…”
Section: Introductionmentioning
confidence: 99%
“…The expanded form has a high surface area and supports thrombus formation throughout its structure. The use of embolic devices based on shape memory polymer in the peripheral vasculature and aorta has been reported 13–15. The shape memory polymer is bioabsorbable,16 although the timeline for absorption is unknown in human clinical cases.…”
Section: Introductionmentioning
confidence: 99%
“… 6 SMP devices have been used for vessel embolization indications. 7 , 8 , 9 , 10 The feasibility of active AAA sac management with SMP during EVAR has been evaluated. 11 We describe the development of preprocedural analysis and intraprocedural techniques to maximize aortic lumen thrombosis with SMP immediately after endograft placement.…”
mentioning
confidence: 99%
“…The authors reported holding the delivery catheter in place until they were sure haemostasis had occurred and the device was stable in the vein. 7 Q: How do you see smart polymer technology being used to the greatest effect in vascular surgery?…”
mentioning
confidence: 99%